Evaluation of calyx senescence during the ripening of ‘ Rojo Brillante’ persimmon by chlorophyll fluorescence imaging - Fathi-Najafabadi, Ayoub; Besada, Cristina; Gil, Rebeca; Calatayud, Ángeles; Salvador, Alejandra (2021)
In persimmon, calyx status is an important fruit quality attribute since it is a very characteristic fruit part from the visual point of view Persimmon fruit possesses a large green four lobed calyx around the fruit stem end, but it darkens during fruit ripening and is associated with commercial quality loss. During calyx senescence, desiccation and browning start from the apical part of sepals toward the base Leaf senescence in plants is related to the breakdown of chloroplast and the degradation of chlorophylls (Lim et al 2007). To date, information about the relation between calyx senescence and physico chemical changes in persimmon during fruit ripening is lacking This information could be useful for determining the harvest time with maximum fruit quality Chlorophyll fluorescence imaging (CFI) is a widespread rapid non intrusive technique to evaluate photosynthetic activity The heterogeneity of photosynthetic activity over the whole leaf area can be analyzed by CFI (Gorbe and Calatayud 2012). The present research aimed to characterize the calyx senescence process during the fruit ripening by CFI, and to establish the relation between CF parameters and the most important fruit quality attributes.